Mechanistic Study of Induced Oxidation of Acetic Acid by As(III) - Zaheer, Ahmed; Farooqui, Mazhar; Ubale, Milind; Kotharkar, Sandeep; Ubale, Sanjay (Asian Journal of Chemistry, 2010)
The mechanistic study of induced oxidation by using As(III) as inductor and acetic acid as acceptor were investigated. A probable mechanism has been suggested on the basis of induction factor (I.F.) It is observed that Mn5+ acts as reactive intermediate and induces the oxidation of acetic acid through anhydride formation.